Trends in research on sick sinus syndrome: A bibliometric analysis from 2000 to 2022 - Zhang, Xin’ai; Zhao, Yong; Zhou, Yutong; Lv, Jiayu; Peng, Jiaran; Zhu, Haiyan; Liu, Ruxiu (Frontiers in Cardiovascular Medicine, 2022)
Sick sinus syndrome (SSS) is a refractory arrhythmia disease caused by the pathological changes of sinoatrial node and its adjacent tissues. 2,251 publications related to SSS were retrieved from Web of Science database from 2000 to 2022 and analyzed by using VOS viewer and CiteSpace software. The results showed the United States dominated the field, followed by Japan, Germany, and China. SSS was closely related to risk factors such as atrial fibrillation and aging. Sick sinus syndrome, atrial fibrillation and sinus node dysfunction were the top three keywords that had the strongest correlation with the study. Pacemaker implantation, differentiation and mutation are research hotspots currently. Clinical studies on SSS found that sick sinus syndrome, atrial fibrillation, and pacemakers were the top three keywords that had the largest nodes and the highest frequency. In the field of basic applied research and basic research, atrial fibrillation and pacemaker cells were the focus of research. In conclusion, bibliometric analysis provided valuable information for the prevention, treatment and future research trends of SSS.